2018
DOI: 10.7759/cureus.3427
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Instance of Simultaneous Infection with Disseminated Nocardia and Pulmonary Aspergillus in a Patient Receiving Treatment with Ibrutinib for Chronic Lymphocytic Leukemia

Abstract: Disseminated Nocardia infections are a rare occurrence that typically occur in immunocompromised hosts. Chronic lymphocytic leukemia (CLL) is a hematologic malignancy which makes patients susceptible to infections through various mechanisms. The treatments for CLL also target immunologic pathways which can contribute to infections. Ibrutinib is a commonly utilized tyrosine kinase inhibitor for CLL which targets the Bruton tyrosine kinase pathway. Although it is generally well tolerated, patients sometimes expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Revealing a predominance of immunocompromised hosts. The instances encompassed cases of immunosuppressive drug therapy, [ 2 , 21 , 31 ] hematologic malignancies, [ 18 , 24 , 25 ] organ transplantation, [ 15 , 16 , 19 , 20 ] chronic granulomatous disease, [ 9 , 14 ] and systemic lupus erythematosus, [ 29 ] and a case of a tooth extraction in a mildly immunosuppressed patient. [ 30 ] Such cases were also observed in nonimmunosuppressed hosts, including patients with diabetes, [ 28 ] allergic disorders, [ 26 ] bronchial thermoplasty therapy [ 27 ] ulcerative colitis during golimumab therapy, [ 23 ] and even accidental drowning incidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revealing a predominance of immunocompromised hosts. The instances encompassed cases of immunosuppressive drug therapy, [ 2 , 21 , 31 ] hematologic malignancies, [ 18 , 24 , 25 ] organ transplantation, [ 15 , 16 , 19 , 20 ] chronic granulomatous disease, [ 9 , 14 ] and systemic lupus erythematosus, [ 29 ] and a case of a tooth extraction in a mildly immunosuppressed patient. [ 30 ] Such cases were also observed in nonimmunosuppressed hosts, including patients with diabetes, [ 28 ] allergic disorders, [ 26 ] bronchial thermoplasty therapy [ 27 ] ulcerative colitis during golimumab therapy, [ 23 ] and even accidental drowning incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Adult onset Still disease with steroid tacrolimus therapy Yamawaki S, [22] 2016 Drowning incident Alonso-Sierra M, [23] 2016 Ulcerative Colitis with Golimumab Therapy, mild chronic obstructive pulmonary disease, bronchiectasis and Hodgkin lymphoma Trastoy R, [24] 2017 B-cell Hodgkin lymphoma and diabetes mellitus. Dotson J, [25] 2018 Chronic Lymphocytic Leukaemia with Ibrutinib therapy Wu J, [26] 2018 Allergic bronchopulmonary aspergillosis, Repeatedly coughed up sputum for 20 y, and history of tuberculosis Matsubayashi S, [27] 2018 Severe asthma with Bronchial thermoplasty therapy and systemic steroids therapy Raj R, [28] 2020 High blood pressure, diabetes Tian X, [9] 2022 X-linked chronic granulomatous disease Roy M, [29] 2022 Systemic lupus erythematosus with hydroxychloroquine and prednisone therapy Jinlin G, [30] 2022 A Mildly Immunosuppressed Patient who had a Tooth Extraction Yan H, [31] 2022 Chronic viral hepatitis B and type 2 diabetes mellitus, highdose glucocorticoids therapy Casale TB, [14] 1984 USA/15/man Pulmonary Not available Carter JM, [15] 1990 USA/49/man Pulmonary Died Monteforte JS, [16] 1993 USA/63/man Pulmonary Recovered well Fernández Peláez JM, [2] 2000 Spain/39/man Pulmonary Died van Dam AP, [17] 2005 Netherlands/22/ man Pulmonary Recovered well Al-Anazi KA, [18] 2008 Saudi Arabia/67/ man Pulmonary Recovered well Hamadani M, [19] 2008 USA/50/woman Pulmonary Recovered well Cabada MM, [20] 2010 USA/65/man Pulmonary Recovered well Misra DP, [21] 2014 India/37/man Pulmonary Recovered well Yamawaki S, [22] 2016 Japan/84/man Pulmonary Died Alonso-Sierra M, [23] 2016 Spain/53/man Pulmonary Not available Trastoy R, [24] 2017 Spain/81/woman Pulmonary Not available Dotson J, [25] 2018 USA/64/woman Bronchopulmonary, subcutaneous tissues, lymph nodes central nervous system Died Wu J, [26] 2018 China/55/woman Pulmonary Recovered well Matsubayashi S, [27] 2018 Japan/35/woman Pulmonary Recovered well Raj R, [28] 2020 India/59/man Pulmonary Recovered well Tian X, [9] 2022 China/3/man Pulmonary, oral maxillofacial, perianal Died Roy M,…”
Section: Reference Predisposing Factorsmentioning
confidence: 99%
“…Interestingly, Rivera et al in 2017 reported a case of paramediastinal abscess in an immunocompetent patient with no known lung disease 8. There have been several case reports of co-infection with Nocardia and Aspergillus to date, but coexisting N. cyriacigeorgica and Aspergillus infection is rarely reported 9–19. This may be partly because N. cyriacigeorgica is a newly identified strain of Nocardia .…”
Section: Discussionmentioning
confidence: 99%